Acclimatization of Nanorobots in Medical Applications Using the Artificial Intelligence System with the Data Transfer Approach. (20th January 2022) - Manoharan, Hariprasath; Teekaraman, Yuvaraja; Kuppusamy, Ramya; Radhakrishnan, Arun; Hariprasath Venkatachalam, K.
Abstract : This article deliberates various issues that are present in the integration of nanorobots in medical applications when real-time arrangements are used. In the current generation, there is a need for a device to recognize different diseases in a fast mode of operation where data transfer should be highly accurate. Even though many devices are existing, valuable information is not provided on the detection segment that has been delivered. Therefore, the technology of nanorobots can be implemented for detecting and providing solutions to various diseases in the human body. These nanorobots operate with gesture actions and they are applied in two different surfaces. Since the robotic technology is implemented in the proposed method, it is necessary to integrate an artificial intelligence (AI) technique in amalgamation with a neural network system which feeds the input in multiple ways using hidden layers. If such arrangements are processed, then, a data transfer path will be communicated with the media access control (MAC) design where the results can be analyzed in a real-time environment using online analysis, and in turn, the outcomes are simulated using MATLAB. Subsequently, comparing the MATLAB exploration with the existing method, it can be observed that the proposed method in the application of the medical field can be prominently improved for an average of 68%.